Distributed UAV-Swarm Control Using BDI Agents - Lima, Bruno de; Silvestre, Iago; Dias, Pedro Henrique; Becker, Leandro Buss; Hübner, Jomi Fred; Brito, Maiquel de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2022)
This paper describes the development of a swarm of autonomous unmanned aerial vehicles (UAVs) that collaborate with each other in forests firefighting. These vehicles are controlled by BDI agents. The solution is distributed and decentralized. Each agent, embedded in a UAV, uses its knowledge and resources to solve a broader problem.